Improving NonViral Gene Delivery Using MHz Bursts of Nanosecond Pulses and Gold Nanoparticles for Electric Field Amplification - Eivina Radzevičiūtė-Valčiukė; Jovita Gečaitė; Augustinas Želvys; Auksė Zinkevičienė; Rokas Žalnėravičius; Veronika Malyško-Ptašinskė; Aušra Nemeikaitė-Čenienė; Vytautas Kašėta; Natalija German; Jurij Novickij; Almira Ramanavičienė; Julita Kulbacka; et al. (MDPI AG, 2023)
Gene delivery by the pulsed electric field is a promising alternative technology for nonviral transfection; however, the application of short pulses (i.e., nanosecond) is extremely limited. In this work, we aimed to show the capability to improve gene delivery using MHz frequency bursts of nanosecond pulses and characterize the potential use of gold nanoparticles (AuNPs: 9, 13, 14, and 22 nm) in this context. We have used bursts of MHz pulses 3/5/7 kV/cm × 300 ns × 100 and compared the efficacy of the parametric protocols to conventional microsecond protocols (100 µs × 8, 1 Hz) separately and in combination with nanoparticles. Furthermore, the effects of pulses and AuNPs on the generation of reactive oxygen species (ROS) were analyzed. It was shown that gene delivery using microsecond protocols could be significantly improved with AuNPs; however, the efficacy is strongly dependent on the surface charge of AuNPs and their size. The capability of local field amplification using AuNPs was also confirmed by finite element method simulation. Finally, it was shown that AuNPs are not effective with nanosecond protocols. However, MHz protocols are still competitive in the context of gene delivery, resulting in low ROS generation, preserved viability, and easier procedure to trigger comparable efficacy.